Shifts in fine‐scale distribution and breeding success of boreal waterbirds along gradients in ice‐out timing and habitat structure - Pöysä, Hannu; Paasivaara, Antti (Blackwell Scientific, 2021)
1. Climate change and other anthropogenic stressors affect freshwater ecosystems worldwide. A prominent manifestation of climate change impacts on aquatic systems at high latitudes is the advance of ice-out date (IOD). Earlier IOD should be advantageous for species such as migratory waterbirds that are dependent on open water to initiate breeding; earlier breeding usually means higher reproductive success. 2. However, advance of IOD may induce phenological mismatches that have negative impacts on the species involved. This may alter habitat dynamics, challenging habitat selection by breeding individuals. An additional challenge is imposed by changes in habitat quality, particularly if preferred habitats deteriorate. 3. Here, we investigated how the fine-scale distribution of breeding individuals and breeding success have changed along gradients in IOD and habitat structure (richness of emergent vegetation) in a boreal waterbird assemblage in southeastern Finland from 1991 to 2018. 4. IOD varied considerably between nearby lakes. The distribution of breeding individuals of the common teal (Anas crecca) and horned grebe (Podiceps auritus) shifted toward lakes with relatively late IOD while Eurasian wigeon (Mareca penelope) and tufted duck (Aythya fuligula) shifted toward lakes with sparse emergent vegetation. Also, breeding success in common teal showed a decreasing trend at lakes with relatively early IOD, while it increased on lakes with relatively late IOD. Success in tufted duck breeding decreased on lakes with rich emergent vegetation, while the opposite was true on lakes with sparse emergent vegetation. The mallard (Anas platyrhynchos) was the only species that did not show a shift in breeding distribution or breeding success along either of the environmental gradients. 5. The findings suggest that a potentially positive climate-driven impact on breeding phenology (earlier IOD) was over-ridden by negative changes in habitat quality. The results underline the need to understand the complexity of the effects of multiple stressors in boreal freshwater ecosystems for their successful management.
Keywords: climate changes; habitat quality; habitat selection; migratory species; waterfowl